Performance analysis on Solar Air Heater with Discrete Arc Shaped Rib Element in Absorber Plate. Issue 1 (November 2020) - Makeshkumar, M.; Thangavel, P.
Abstract: Solar Air Heater (SAH) absorbs the irradiation and converts it into thermal energy, which is supplied to flowing fluid for the purpose of drying agricultural products, curing of industrial products, space heating applications and so on. An experimental examination has been conducted to assess the thermal performance of SAH having discrete arc shaped rib element in the absorber plate and analyzed against Flat Plate Solar Air Heater (FPSAH). Performance has been assessed by identifying the various parameters like useful heat gain, surface temperatures of collector plate, flow rate of working fluid, temperatures of air at inlet and exit. Investigation has been performed for flow rates of 0.028 kg/s and 0.045 kg/s. The results indicate that the absorber plate with artificial roughness element shows considerable increase in exit air temperature, heat transfer rate and thermal efficiency. Thermal efficiency of about 70 % is obtained for 0.045 kg/s, which is 13.1% more than that of FPSAH.